REPETISI DALAM TAJUK RENCANA SUARA MERDEKA 1998-2004: DEKONSTRUKSI BAHASA PERS ERA REFORMASI - Nikolaus Rendi Prasetya Hadi; Sintaria Kusumaningrum; Slavian O Delastyanto (Universitas Aki, 2021)
The focus of the research was to describe repetition in Editorial of Suara Merdeka 1998-2004 edition as the characteristic of the press language in the reform era. This was a qualitative descriptive research. The researcher gathered data by observing from its lexical cohesion aspects and classifying based on its repetition. The result of the data in this study found that press language in reform era presented reliable and transparent information, and on the contrary it shows the big distinction during new order era which was euphemistic. The press presented actual topics and dare to break-through delivering the news which dealt with the press prohibition era at that time.